1988
DOI: 10.1080/00021369.1988.10869025
|View full text |Cite
|
Sign up to set email alerts
|

Methyl Epijasmonate in the Essential Oil of Tea

Abstract: Methyl epijasmonate has a 400 times stronger aroma than methyl jasmonate, which is known to be one of the key compounds in the aroma of tea, and the former is easily isomerized on heating. Reinvestigation of the separation and identification of tea aroma compoundsindicated that steam distillation should be performed under reduced pressure, and that the gas chromatographic conditions should be controlled at below 170°C using an open tubular column coated with a non-polar liquid phase to avoid the isomerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…We concluded therefore that the injection temperature used during the GC analysis did not appear to bring about the epimerization from (±)-epiMJ to (±)-MJ and, in short, any value might be equally set during the experimentation. These results are in disagreement with those reported by other authors, who have described the conversion of (±)-epiMJ to (±)-MJ when working at column temperatures >180 °C and injection temperatures >170 °C , . This discrepancy might be due to the distinct chromatographic conditions other than the temperatures used in these works with respect to the present study (i.e., column length, carrier gas, etc.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…We concluded therefore that the injection temperature used during the GC analysis did not appear to bring about the epimerization from (±)-epiMJ to (±)-MJ and, in short, any value might be equally set during the experimentation. These results are in disagreement with those reported by other authors, who have described the conversion of (±)-epiMJ to (±)-MJ when working at column temperatures >180 °C and injection temperatures >170 °C , . This discrepancy might be due to the distinct chromatographic conditions other than the temperatures used in these works with respect to the present study (i.e., column length, carrier gas, etc.…”
Section: Resultscontrasting
confidence: 99%
“…Selection of the GC conditions. Taking into account that epiMJ has already been reported to be isomerized to MJ above 180 °C (13,17), a study on the conditions to be used during the chromatographic analysis was considered to be mandatory. The study was faced in such a way that a standard solution of MJ, made up of 95% (()-MJ and 5% (()-epiMJ, in methanol was injected into GC at different injection temperatures, as previously specified under Materials and Methods, the oven temperature being 170 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The oven temperature was held at 60 °C for 4 min and then increased to 180 °C at a rate of 3 °C/min. The injector and detector temperatures were set at 170 °C and 180 °C, respectively, because it has been reported that methyl epijasmonate and its isomers, which are important aroma compounds in tea, were significantly isomerized or decomposed at higher than 180 °C (8).…”
Section: Introductionmentioning
confidence: 99%
“…Typically during aging and mechanical injury, the hydrolysis of lipids by lipases and the formation of 9- and 13- hydroperoxide intermediates decisively formed “fresh-green” compounds such as ( Z )-3-hexenol, ( E )-2-hexenal, hexanal, and other related products have been confirmed ( ). Also, characterization of the most odoriferous epi -methyl jasmonate in the seasonal flavors and in oolong tea has unequivocally proved their formation is influenced by environmental and processing conditions ( , ). Independently, these naturally occurring plant pheromones were biologically synthesized from linolenic acid, lipoxygenase, cyclization of hydroperoxide, and β-oxidation ().…”
Section: Introductionmentioning
confidence: 99%